2002
DOI: 10.1063/1.1432123
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties in LiMn2O4, Li0.95Mn2O4, and LiMn1.95B0.05O4 (B=Al or Ga) around room temperature

Abstract: Low temperature dielectric properties of YMn 0.95 Ru 0.05 O 3 AIP Conf. Correlation between high ionic conductivity and twin structure of La 0.95 Sr 0.05 Ga 0.9 Mg 0.1 O 3 − δ Nature of small-polaron hopping conduction and the effect of Cr doping on the transport properties of rare-earth manganite La 0.5 Pb 0.5 Mn 1−x Cr x O 3In order to identify the carrier responsible for the electrical transport at room temperature in LiMn 2 O 4 from the viewpoint of practical applications as a cathode material, the bulk co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 37 publications
5
32
1
Order By: Relevance
“…Hence, it is concluded that the conductivity in spinel LiMn 2 O 4 nanorods is mainly due to electrical conduction in grains. The observed activation energy for spinel LiMn 2 O 4 nanorods is comparable to the reported values (0.39 eV,0.38 eV, 0.42 eV)[37,41,42].…”
supporting
confidence: 91%
“…Hence, it is concluded that the conductivity in spinel LiMn 2 O 4 nanorods is mainly due to electrical conduction in grains. The observed activation energy for spinel LiMn 2 O 4 nanorods is comparable to the reported values (0.39 eV,0.38 eV, 0.42 eV)[37,41,42].…”
supporting
confidence: 91%
“…Charge transport is expected to take place in the form of incoherent motion via adiabatic small-polaron hopping between eg orbitals of the Ni ions; this mechanism is characteristic of many oxides, and has been evidenced in LiMn2O4. [29][30][31][32][33] A small polaron manifests in an ionic solid as a point charge accompanied by a local distortion of the ions around that charge. 34,35 This distortion creates a selftrapping effect in which the charge carrier is at the bottom of a potential well created by its presence through electron-phonon coupling.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…However, the lock-in detection system of the microscope can measure other AC-mediated responses as explained in Section I. Taking into account that LiMn 2 O 4 is a small polaron semiconductor, 27 an additional contribution can emerge from AC mediated dipoles. Chen et al 35 suggested that voltage spectroscopy hysteresis loops can be used to distinguish between polar and non-polar contributions.…”
Section: Resultsmentioning
confidence: 99%
“…1, [26][27][28] It was theoretically shown that the polaron hopping can impact lithium ion movements 28 and experimentally deduced that lithium diffusivity is intrinsically related to the polaronic properties. 29 As this coupling is little understood and it is hard to quantify, it will be reserved to future studies.…”
Section: A Thermodynamical Descriptionmentioning
confidence: 99%